2015
DOI: 10.3892/ol.2015.3591
|View full text |Cite
|
Sign up to set email alerts
|

FOLFIRINOX-induced reversible dysarthria: A case report and review of previous cases

Abstract: Abstract. FOLFIRINOX is a standard chemotherapeutic regimen for patients with advanced pancreatic cancer who have a good performance status. In this study, we present the case of a 64-year-old male who developed dysarthria following FOLFIRINOX treatment, and review all four cases of dysarthria encountered among the nine patients who received this treatment in our hospital. In all cases, dysarthria occurred during the infusion of irinotecan in the first course of treatment, persisted for several hours, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…To date, 29 cases of transient dysarthria and/ or aphasia observed during or shortly following the administration of irinotecan have been reported in the literature and are summarized in Table 1 [12][13][14][15][16][17][18][19][20][21]27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, 29 cases of transient dysarthria and/ or aphasia observed during or shortly following the administration of irinotecan have been reported in the literature and are summarized in Table 1 [12][13][14][15][16][17][18][19][20][21]27].…”
Section: Discussionmentioning
confidence: 99%
“…In all reported cases [12][13][14][15][16][17][18][19][20][21], clinical signs were stable and neurological examinations showed no evidence of neurological abnormalities, except dysarthria. Patients were monitored carefully and observed to return close to their baseline status within 1-2 h.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is commonly performed but rarely yields additional information. The measures described in the literature to alleviate this symptomatology are shown in Table 1 [8,9,11,[14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Transient dysarthria and blepharospasm are rare toxicities of irinotecan infusion, first recognized during the FOLFIRINOX infusion by Gunturu et al 49 Japanese investigators observed no cases of dysarthria in clinical trials of FOLFOXIRI in advanced colorectal cancer. 50 In this regimen, irinotecan is administered prior to oxaliplatin. They suggested that the FOLFIRINOX-induced dysarthria may be associated with the sequence of drug administration: intravenous infusion of oxaliplatin, immediately followed by leucovorin, followed by 30 min irinotecan.…”
Section: Management Of Toxicitiesmentioning
confidence: 99%